PENGRUSAKAN TEMPAT BERSEJARAH DALAM PERANG ANTARNEGARA SEBAGAI PELANGGARAN HUKUM HUMANITER INTERNASIONAL - Sitanggang, Dyan (Universitas Sam Ratulangi, 2013)
Cultural property, in this present case: historical object, is protected and respected as world’s asset with great value in international law especially international humanitarian law through its various institutions and instruments. The historical object with great importance to humanity has to be protected at all times and deserves international protection. However, some people oftentimes forget its obligation and intentionally destroy such objects, even though they are well aware that States and people have the obligation to protect, respect and safeguard those objects. Hague Convention 1954 boldly states that the destruction of such objects is a violation of customs of law and international humanitarian law. Keywords: Destruction, cultural property, historical object, armed conflict, international humanitarian law